Modeling and analysis of a simple manufacturing-oriented multi-agent system - P. Levi; M. Schanz; V. Avrutin (Discrete Dynamics in Nature and Society)
Due to the autonomy of individual agents and the use of the concept of distributed planning, multi-agent systems (MAS) represent a promising approach to achieve fault-tolerant self-organizing manufacturing systems. In this article, a basic component of a manufacturing-oriented MAS is presented. The negotiation strategies are formulated in such a way that they, on the one hand, guarantee considerable flexibility of the basic component itself, and, on the other hand, enable the construction of more complex systems built up from several components. On the basis of this single component, it is shown that the dynamics of such systems without appropriate control mechanisms can be chaotic. Such behaviour is, however, unwanted in practice and must therefore be stabilized or avoided. In order to develop appropriate tools for this task, the dynamic behaviour of the system is investigated using concepts and methods of synergetics and the theory of nonlinear dynamical systems.